The Prenylflavonoid ENDF1 Overrules Central Nervous System Growth Inhibitors and Facilitates Regeneration of DRG Neurons - Bieler, Lara; Vogl, Michael; Kirchinger, Michael; Urmann, Corinna; Riepl, Herbert; Bandtlow, Christine; Klimaschewski, Lars; Aigner, Ludwig; Couillard-Despres, Sebastien (Frontiers in Cellular Neuroscience, 2019)
Restoration of neuronal connectivity after lesion of the central nervous system, such as spinal cord injury, is one of the biggest challenges in modern medicine. In particular, the accumulation of axon growth inhibitory factors at the site of injury constitutes a major obstacle to structural and thus functional repair. We previously investigated a group of prenylflavonoids derived from hops for their capacity to promote neuroregeneration and identified a molecule called ENDF1 that was very potent to enhance regrowth and branching of neurites from dorsal root ganglion neurons in culture on growth promoting substrates. In the present study, we investigated ENDF1's capacity to promote regeneration of rat dorsal root ganglion neurons in vitro in the presence of three main components of the extracellular matrix acting as axon growth inhibitors: Semaphorin3A, EphrinA4 and mixed chondroitin sulphate proteoglycans. We report that ENDF1 application significantly promoted the percentages of sensory neurons able to regrow their neurites regardless of the presence of those inhibitors, and this to an extent similar to the one obtained after NGF treatment. Moreover, ENDF1 strongly enhanced the total neurite length and the complexity of neurites extending from neurons challenged with axon growth inhibitors. Importantly, although the impact of NGF and ENDF1 on the regeneration of neurons was similar, the regenerative activity of ENDF1 was not compromised by an inhibitor of the NGF receptor TrkA (GW441756), indicating that ENDF1 and NGF act through different signaling pathways.